Human Resource Management in The Context Of Higher Education: Strategies for Developing the Potential of Academic and Non-Academic Employees - Maya Citra (Al-Fikru: Jurnal Ilmiah, 2023)
The quality of higher education is determined one of them through the development of human resource potential. with regard to that this study aims to analyze the strategy of developing the potential of academic and non-academic staff and the obstacles faced. This research was conducted at STEBIS Al-Ulum Terpadu Medan. Data collection techniques using observation, interviews and documentation studies. Data analysis uses data collection techniques, data reduction, data presentation, and conclusion drawing. The results revealed that the Strategy for Developing the Potential of Academic and Non-Academic Employees through the steps of mapping development needs, planning development programs, program implementation, evaluation and monitoring, support and motivation, career development, equal opportunities. What is faced are obstacles in strategy formulation, budget limitations, resistance or disapproval from employees to development programs, lack of understanding and support from the leadership of educational institutions, lack of infrastructure and technology, gaps in needs, lack of periodic evaluation and monitoring, differences in organizational culture and lack of integration between work units.